Identification of specifically reduced Th2 cell subsets in allergic rhinitis patients after sublingual immunotherapy. Issue 9 (30th August 2018) - Ihara, F.; Sakurai, D.; Yonekura, S.; Iinuma, T.; Yagi, R.; Sakurai, T.; Ito, T.; Matsuura, A.; Morimoto, Y.; Arai, T.; Suzuki, S.; Katayama, K.; et al.
Abstract: Background: Although Th2 cells are well known to play important roles in allergic diseases including allergic rhinitis (AR), the factors that induce and sustain the pathogenesis of AR remain unclear. The recent development of sublingual immunotherapy (SLIT) is expected to allow changes to the underlying pathogenesis of AR. However, which Th2 cell subsets are important in house dust mite‐induced AR (HDM‐AR), the influence of SLIT on the pathogenic Th2 cells, and the association of Th2 cell subsets with SLIT efficacy have not been clarified. Methods: The cytokine production and frequency of HDM‐reactive T‐cell subsets in peripheral blood mononuclear cells (PBMCs) were evaluated using flow cytometry in 89 HDM‐AR patients (placebo [n = 43] and HDM 300 IR [n = 46]) who participated in a placebo‐controlled study of SLIT with HDM tablets. All patients provided samples both before treatment as a baseline and at the end of the 52‐week study. The PBMCs were stained with CellTrace™ Violet (CTV) before culture with HDM extract, and HDM‐reactive T cells were detected as the proliferated cells with diminished CTV. Results: HDM‐reactive IL‐5 + IL‐13 + CD27 − CD161 + CD4 + cells and ST2 + CD45RO + CD4 + cells were observed in the peripheral blood from each patient with HDM‐AR; these cells significantly decreased after SLIT in the group treated with active tablets. HDM‐reactive ST2 + CD45RO + CD4 + cells were significantly lower in active‐responders. Conclusion: Allergen‐reactive ST2 + CD45RO + CD4 + cells or those combined with IL‐5 + IL‐13 + CD27 − CD161 + CD4 + cells may be useful as markers indicating the successful treatment of SLIT. These cells may play a crucial role in the pathogenesis of AR as pathogenic memory Th2 cells. Abstract : House dust mite (HDM)‐reactive IL‐5 + IL‐13 + CD27 − CD161 + CD4 + cells and ST2 + CD45RO + CD4 + cells were observed in the peripheral blood from patient with HDM‐induced allergic rhinitis; these cells significantly decreased after sublingual immunotherapy. HDM‐reactive ST2 + CD45RO + CD4 + cells were significantly lower after 1 year of sublingual immunotherapy in the responders in active group than those for the nonresponders. Allergen‐reactive ST2 + CD45RO + CD4 + cells or those combined with IL‐5 + IL‐13 + CD27 − CD161 + CD4 + cells may be useful as markers indicating the successful treatment of sublingual immunotherapy.